PROTOTIPE PERANCANGAN ULANG RAK PENDINGIN ROTI DENGAN MENGGUNAKAN METODE VEREIN DEUTCHER INGENIEURE 2222 - Michelle Febri (Jurnal Disprotek, 2021)
MSME AAA Bakery is a home industry produces white bread. This MSME produces every day to fulfil customer demand. However, there is waste in the production activities of MSME AAA Bakery, namely in the form of a relatively longer cooling time, cooling time for fresh bread between 120 minutes to 180 minutes, while at MSME AAA Bakery the cooling time for bread is 231 minutes on average. This is due to the initial rack design that hinders the cooling process. The purpose of this study was to minimize the cooling time of the bread with a prototype of a bread cooling rack redesign. The method used is Verein Deutcher Ingenieuer 2222, because it can provide a solution to the problem of long bread cooling time by redesigning the bread cooling rack. So that the relatively long cooling time of bread can be minimized and there is no long waiting time for bread production activities at MSME AAA Bakery. The results of the redesigned prototype of the bread cooling rack showed that there was a differences in the cooling time of the bread. In the experiment with the redesigned shelf prototype, the cooling time of the bread was around 90 minutes.